Mortality Effects of Hypothetical Interventions on Physical Activity and TV Viewing. Issue 2 (February 2021) - YANG, YI; HODGE, ALLISON M.; DUGUÉ, PIERRE-ANTOINE; WILLIAMSON, ELIZABETH J.; GARDINER, PAUL A.; BARR, ELIZABETH L. M.; OWEN, NEVILLE; DUNSTAN, DAVID W.; LYNCH, BRIGID M.; ENGLISH, DALLAS R.
ABSTRACT: Introduction: Long-term effects of physical activity and television (TV) viewing on mortality have been inferred from observational studies. The associations observed do not allow for inferences about the effects of population interventions and could be subject to bias due to time-varying confounding. Methods: Using data from the Australian Diabetes, Obesity and Lifestyle Study, collected in 1999–2000 (T0), 2004–2005 (T1), and 2011–2012 (T2), we applied the parametric g-formula to estimate cumulative risks of death under hypothetical interventions on physical activity and/or TV viewing determined from self-report while adjusting for time-varying confounding. Results: In the 6377 participants followed up for 13 yr from 2004 to 2005 to death or censoring in 2017, 781 participants died. The observed cumulative risk of death was 12.2%. The most effective hypothetical intervention was to increase weekly physical activity to >300 min (risk ratio (RR), 0.66 (0.46–0.86) compared with a "worst-case" scenario; RR, 0.83 (0.73–0.94) compared with no intervention). Reducing daily TV viewing to <2 h in addition to physical activity interventions did not show added survival benefits. Reducing TV viewing alone was least effective in reducing mortality (RR, 0.85 (0.60–1.10) compared with the worst-case scenario; RR, 1.06 (0.93–1.20) compared with no intervention). Conclusions: Our findings suggested that sustained interventions to increase physical activity could lower all-cause mortality over a 13-yr period, and there might be limited gain from intervening to reduce TV viewing time in a relatively healthy population. Abstract : Supplemental digital content is available in the text.